2010
DOI: 10.1371/journal.pone.0009004
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism Accentuates Children's Conversational Understanding

Abstract: BackgroundAlthough bilingualism is prevalent throughout the world, little is known about the extent to which it influences children's conversational understanding. Our investigation involved children aged 3–6 years exposed to one or more of four major languages: English, German, Italian, and Japanese. In two experiments, we examined the children's ability to identify responses to questions as violations of conversational maxims (to be informative and avoid redundancy, to speak the truth, be relevant, and be po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 51 publications
4
58
4
1
Order By: Relevance
“…Studies looking at the influence of bilingualism on pragmatic competence more generally (Siegal, Iozzi, & Surian, ; Siegal et al., ; Surian, Tedoldi, & Siegal, ) have indeed indicated a bilingual advantage. Moreover, the SI task is considered to be a metalinguistic task (Siegal et al., ) and bilingual children have been previously reported to outperform their monolingual peers in other metalinguistic tasks (e.g., Bialystok, ). In common with many other studies of bilingualism, however, none of these studies matched monolingual and bilingual participants on SES, so the potential contributions of bilingual status and SES remain to be disentangled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at the influence of bilingualism on pragmatic competence more generally (Siegal, Iozzi, & Surian, ; Siegal et al., ; Surian, Tedoldi, & Siegal, ) have indeed indicated a bilingual advantage. Moreover, the SI task is considered to be a metalinguistic task (Siegal et al., ) and bilingual children have been previously reported to outperform their monolingual peers in other metalinguistic tasks (e.g., Bialystok, ). In common with many other studies of bilingualism, however, none of these studies matched monolingual and bilingual participants on SES, so the potential contributions of bilingual status and SES remain to be disentangled.…”
Section: Methodsmentioning
confidence: 99%
“…It could be the case then that Experiment 1 failed to detect a bilingual attentional benefit because the bilingual effect actually lies in pragmatic ability and not in attention per se, as also suggested by Siegal et al (2007). Studies looking at the influence of bilingualism on pragmatic competence more generally (Siegal, Iozzi, & Surian, 2009;Siegal et al, 2010;Surian, Tedoldi, & Siegal, 2010) have indeed indicated a bilingual advantage. Moreover, the SI task is considered to be a metalinguistic task and bilingual children have been previously reported to outperform their monolingual peers in other metalinguistic tasks (e.g., Bialystok, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen out of those 23 children judged (all four) underinformative some test items as felicitous. Siegal et al (2010) in their bilingual study also found that monolingual Japanese children are not as sensitive to violations of the Quantity maxim as they are to those of the Relation maxim. I do not emphasize this result because it is not clear on what type of Quantitybased (under)informativeness children were examined.…”
Section: Resultsmentioning
confidence: 89%
“…For example, Siegal et al (2009Siegal et al ( , 2010 have observed that bilingual children between the ages of 3 and 6 have a better conversational understanding than their monolingual peers, as indicated by their greater sensitivity to violations of conversational maxims (i.e. speakers must be informative while avoiding redundancy, and they must speak the truth and be relevant and polite; Grice, 1975).…”
Section: Could Bilingualism Help Theory Of Mind Development?mentioning
confidence: 99%